Information media literacy in the education of communication students in Mexico: Case of a college in northeastern Mexico - Garza Sánchez, Juan Antonio; Saucedo Espinosa, Francisco (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
The development of communication is an area of study of global importance and with the development and rise of information technologies, that have become new social paradigms, are a cause of the processes of change driven by the greater circulation of information and communication in a global environment. In this environment, media literacy, seen as a progressive domain promoting communication, has been a challenge in their practice and research. The present article offers a proposal to incorporate academic and digital literacy processes in university classrooms, thus converting these into attractive and real practices adapted to the new educational challenges.